Pancasila as a National Development Paradigm in Community, Nation and State Life - Wiwik Eka Kusmawati; Riyanti Eka Putri; Masduki Asbari (AGUSPATI RESEARCH INSTITUTA, 2022)
This paper aims to find out Pancasila as a paradigm of national development in the life of society, nation, and state. From the title of this paper, it can be concluded that Pancasila as a paradigm has a close relationship with the life of society, nation, and state. To achieve the goals in life as a nation and state, the Indonesian people carry out national development, this is intended to increase the dignity of the nation in the international world. Pancasila as a national development paradigm has the intention that every national development must be based on the morality of the Pancasila precepts. As well as the nature of cooperation, helping each other, sharing and collaborating with the Indonesian people in society regardless of race, ethnicity, or religion is not spared from the role of the contents of the third principle of Pancasila.